Robotic evolution from Si to Xi in rectal cancer assessing operative performance and oncological outcomes - Wang, Wenpeng; Gao, Shan; Huang, Jinghao; Yun, Duo; Wang, Jiefu (Frontiers in Surgery, 2026)
PurposeTo compare perioperative and oncologic outcomes between robotic surgical platforms (Si vs. Xi) in rectal carcinoma.MethodsA retrospective cohort study of 86 robotic rectal cancer resections (Si: n = 31; Xi: n = 55) were analyzed at Tianjin Medical University Cancer Hospital between November 2019 and June 2024.ResultsAmong 86 patients with comparable baseline clinicopathological variables (all p > 0.05), the Xi system showed superior perioperative efficiency: shorter operation (226.7 vs. 282.1 min, p = 0.010), console (p = 0.016) and docking times (p = 0.013), less blood loss (83.8 vs. 155.8 mL, p = 0.005), and a shorter postoperative stay (7.8 vs. 9.7 days, p = 0.016). On multivariable analyses, Xi remained independently associated with a shorter operative time (p = 0.002), reduced blood loss (p = 0.027), and decreased length of stay (p = 0.038). Complication rates, lymph node yield, and short-term oncologic quality indicators (distal resection margin [DRM], circumferential resection margin [CRM], mesorectal integrity) were comparable between two systems (all p > 0.05). In low rectal cancers (≤ 5 cm from the anal verge) with balanced baselines, Xi achieved a higher sphincter preservation rate (90.5% vs. 55.6%, p = 0.049). Survival trends numerically favored Xi (3-year DFS 79.8% vs. 73.0%; OS 92.0% vs. 83.0%), but differences were not significant (DFS: p = 0.54; OS: p = 0.26). On Cox regression, TNM stage independently predicted both DFS (p = 0.041) and OS (p = 0.029). However, the robotic platform (Xi vs. Si) showed no survival advantage (DFS: HR = 1.33, 95% CI 0.53–3.37, p = 0.548; OS: HR = 1.43, 95% CI 0.76–2.67, p = 0.267).ConclusionsCompared with Si, the Xi platform confers measurable perioperative advantages—shorter operative time, less blood loss, and reduced hospitalization—without compromising short-term oncologic quality or survival. In low rectal tumors, Xi may facilitate sphincter preservation under comparable baselines. Long-term outcomes appear driven primarily by disease stage rather than platform generation.